2011
DOI: 10.1186/1471-2458-11-661
|View full text |Cite
|
Sign up to set email alerts
|

The stigma of obesity in the general public and its implications for public health - a systematic review

Abstract: BackgroundUp to this date, prevalence rates of obesity are still rising. Aside from co-morbid diseases, perceived discrimination and stigmatization leads to worsen outcomes in obese individuals. Higher stigmatizing attitudes towards obese individuals may also result in less support of preventive and interventive measures. In light of the immense burden of obesity on health care systems and also on the individuals' quality of life, accepted and subsidized preventive measures are needed. Policy support might be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
103
1
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(117 citation statements)
references
References 32 publications
4
103
1
9
Order By: Relevance
“…Population-based surveys in Denmark, Germany, Australia and the USA have also shown less public support for regulation and taxation (13)(14)(15)(16) . One explanation for the low support for more intensive government intervention may be the perceived causes of overweight and obesity (17) . The pervasive stereotypes and stigma surrounding obesity may mean that it is still seen as 'the person's own fault', leading to objections against public expenditure because the condition is perceived to be 'self-inflicted'.…”
mentioning
confidence: 99%
“…Population-based surveys in Denmark, Germany, Australia and the USA have also shown less public support for regulation and taxation (13)(14)(15)(16) . One explanation for the low support for more intensive government intervention may be the perceived causes of overweight and obesity (17) . The pervasive stereotypes and stigma surrounding obesity may mean that it is still seen as 'the person's own fault', leading to objections against public expenditure because the condition is perceived to be 'self-inflicted'.…”
mentioning
confidence: 99%
“…This incongruence in care patterns across medical disciplines is likely multifactorial. One potential reason is likely the aforementioned hesitance to undergo evaluation and care due to perceived stigma against the obese and overweight from the healthcare system and practitioners,2, 4, 8, 35, 36 resulting in fewer opportunities to establish and optimize medical therapy. As referral for PCI ensures contact with the healthcare system, this may explain the differences from prior analyses.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to remark that some investigations have showed that antifat attitudes do not help obese people to have a healthy life and that the stigmatization of obese individuals has important implications for public health policies (see for a review: Sikorski et al, 2011). For these reasons, we believe that it is especially important to analyze which are the roots of the prejudice toward obese individuals.…”
Section: Discussionmentioning
confidence: 99%